THE PRIORITIES OF STATE TAX POLICY IN UKRAINE - SHVABII, Kostyantyn (Scientific journal «World of Finance», 2021)
Introduction. Successful government decisions in the budget and tax areas able to provide socio-economic development of the country. Ukraine has undergone many tax reforms since independence, but there is no sustainable socio-economic growth. In view of this, it is important to clarify the directions of transformation of the state tax policy. The purpose of the article is to determine the directions of transformation of the tax policy of the state in Ukraine in the medium term based on the analysis of the existing structural disparities of the domestic economy and its taxation system. Results. The research sets out the areas of state tax policy transformation for medium-term perspective. The proposals presented here are to transform the state tax policy aimed at forming a tax system in Ukraine that will promote long-term, balanced, inclusive economic growth and, at the same time, provide a sufficient level of state revenues to perform its functions. To do this, in our opinion, in the medium term there should be a general redistribution of the tax burden by applying the entire list of taxes and their constituent elements (taxpayers, objects of taxation, tax base, benefits, tax rates, etc.), which should lead to the elimination of disparities in the tax system of Ukraine, and will contribute to structural modernization of the domestic economy in the long run and increase the level of voluntary tax payments. These proposals mainly concern changes in the structure of the tax system and elements of taxes, and do not concern the corresponding changes in the system of their administration, as this is the subject of a separate discussion. Conclusions. Given the existing structural disparities in the tax system of Ukraine, which lead to a regressive distribution of the tax burden by income level, one of the priority measures of state tax policy is to reduce the regulatory VAT rate from 20% to 15%. This will support the purchasing power of domestic households. The main positive side effect of this is to create such conditions for taxpayers, under which further activities on the schemes of formation of fictitious tax credit becomes economically unprofitable.